Innovation in the adoption of the electronic judicial process – EJP - Neves, Jomar Nascimento; Arruda Filho, Emílio José Montero (Revista de Administração da UFSM, 2020)
This article analyzes a case study of technological innovation with the use of the Electronic Judicial Process - EJP, occurred in the 8th Regional Labor Court, in the 8th Brazilian Judicial District, in Belém, capital of the state of Pará (PA). The research adopted a qualitative and exploratory approach, carrying out interviews with users and actors who maintain the innovation process. The conclusions reflect, evaluate and describe the path of acceptance, adoption, and diffusion of the Electronic Judicial Process, following the stages developed by Roger’s theory regarding the process of innovation’s diffusion and adoption. The study identified that users are loyal to the EJP and they do not show any intention of replacing it, for example, with the tool that was in place before the EJP use. In addition, the study reveals the perception of the importance and superiority of the platform, adding more value to the innovative process, even observing that there were difficulties at the beginning of the adoption. The research showed that users perceived a reduction in the working time, which contributed for each individual become a potential actor in the process of adoption and diffusion of the innovation proposed within the Labor Court of Belém.